Comparing the corneal temperature of dry eyes with that of normal eyes via high-resolution infrared thermography - Wu, Chunbo; Huang, Yuanshen; Xu, Banglian; Li, Baicheng; Zhuang, Songlin; Cao, Guofan; Hu, Yan; Gu, Zhensheng (Frontiers in Medicine, 2025)
PurposeThis study compares the corneal temperature in dry eyes with normal eyes via high-resolution infrared thermography.MethodsA total of 86 participants were enrolled, with 40 and 46 participants in the dry eye disease (DED) and control groups, respectively. All participants underwent non-invasive breakup time (NIBUT) measurement, an Ocular Surface Disease Index (OSDI) questionnaire and ocular thermography.ResultsIn the DED group, the mean initial central corneal temperature (initial CCT) is 33.25 ± 0.66°C, the tenth-second central corneal temperature (10s-CCT) is 32.47 ± 0.84°C, and the mean change in central corneal temperature measured within 10 s (change in CCT within 10 s) is 0.78 ± 0.30°C. For the controls, the initial CCT, 10s-CCT, and change in CCT within 10 s are 33.14 ± 1.02°C, 32.90 ± 0.99°C, and 0.23 ± 0.20°C, respectively. Except for the initial CCT (p = 0.549), significant differences are observed in the 10s-CCT (p = 0.034) and the change in CCT within 10 s (p < 0.001) between the two groups. The standard deviation of the temperature values within the region of interest (SD of TVs within ROI) on the central cornea is calculated to compare the uniformity of corneal temperature. In the DED group, the mean standard deviation of the initial temperature values within the region of interest (SD of initial TVs within ROI) is similar to that in the control group (0.23 ± 0.07°C vs. 0.22 ± 0.05°C, p = 0.926). In contrast, the mean standard deviation of the tenth-second temperature values within the region of interest (SD of 10s-TVs within ROI) in the DED group is greater than that in the control group, and there is a significant difference (0.44 ± 0.20°C vs. 0.35 ± 0.15°C, p = 0.016). In the DED group, the mean change in CCT within 3 s after tear film break-up is significantly greater than that before tear film break-up (0.19 ± 0.08°C vs. 0.10 ± 0.10°C, p < 0.001).ConclusionAs the time with eyes open increases, dry eyes present a significantly faster decrease in central corneal temperature (CCT) and a significantly worse uniformity of corneal temperature compared with normal eyes.